IV. Bisphosphonates promote healing of complicated stress fractures in the foot - E Fink-Eriksen; T Ianssen; EE Husebye (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2021)
Delayed healing of stress fractures constitutes a significant clinical problem causing pain and disability for the patients affected. The vast majority heal after immobilization of the extremity affected, but a certain small number of patients display delayed union despite standard treatment, resulting in prolonged disability and usually end up needing orthopedic procedures to get symptomatic relief. All stress fractures exhibit Bone Marrow Edema or Bone Marrow Lesions (BMLs) with and without fracture lines on MRI, and in cases of delayed union these lesions persist. Thus, it is conceivable that BML formation might contribute to non-union. Previous studies on transient osteoporosis and osteoarthritis have demonstrated that bisphosphonates can reduce BMLs. We therefore wanted to test, whether treatment with IV. Bisphosphonates could promote healing of such fractures. In this study we report our clinical experience and the results obtained after treating 8 patients exhibiting delayed healing an off label protocol using two Zoledronic acid infusions (given 3 months apart).  Seven female and one male patient (aged 30-72) were enrolled. All had signs of non-union for more than 12 months (defined as continued pain, disability and persistent BMLs on MRI). Pain was monitored using VAS (1-10) and MRI was performed in six of the patients at baseline, 3, 6 and 12 months after the first infusion. All patients received Ca (0.5-1 g Ca per day) and vitamin D supplementation (800-1000 IE per day). All patients experienced clinical healing with significant reduction of pain at the fracture site and improvement of ambulation within 1-3 months after the first infusion. 4 patients experienced further reducgtion of pain after the second infusion. At 6 months, ambulatory functions were completely restored in all patients and a highly significant reduction of VAS scores from an average of 7.3 before treatment to 1.1 at 6 months and 0,9 at 12 months (P<0,0001) could be demonstrated. The alleviation of pain was accompanied by reduction or total resolution of BMLs on MRI. Except for 2 cases of flu-like symptoms after the first infusion, no adverse effects were recorded.  In conclusion, In conclusion, 2 infusions of zoledronic acid (5 mg) given 3 months apart, may emerge as a possible treatment modality of stress fractures in the foot showing delayed union, and could potentially reduce the need for more extensive surgical intervention in such complicated cases. This small observational pilot study needs to be corroborated in a larger randomized, controlled trial.